Terra sigillata from Žuta Lokva (Dalmatia, Croatia) - Ožanić Roguljić, Ivana; Mantovani, Valentina (Rei Cretariae Romanae Fautorum Acta, 2024)
In this paper, we are studying terra sigillata from the roadside station Žuta Lokva. The site was positioned in the hinterland of the province of Dalmatia. In Roman times, this site was set by a road mentioned in Itinerarium Antonini Augusti Ad Aquileia per Liburniam Sisciam. Today, it is stationed a few meters from a crossroad, Senj-Otočac-Brinje. The presence of the of terra sigillata liscia forms seems consistent with Po Valley decorated production already analysed and published. One 126 terra sigillata Italica liscia shards have been found: 117 Po Valley production and five Arezzo production. The most common forms are cups Consp. 26, 27 and plates Consp. 20.4. Four stamps have been identified, but the only integral stamp is MACER in pl. pedis (Macer, OCK 1079) on a dish bottom of an undetermined shape.